Metabolomics profiling of fermented cantaloupe juice and the potential application to extend the shelf life of fresh cantaloupe juice for six months at 8°C - Muhialdin, Belal J.; Kadum, Hana; Meor Hussin, Anis Shobirin (Elsevier, 2021)
The aim of this study was to evaluate the potential of adding fermented cantaloupe juice at different concentrations to extend the shelf life of fresh cantaloupe juice stored at 8 °C for six months. Cantaloupe juice was fermented with Lactobacillus plantarum FBS05 for 48 h at 37 °C. The antimicrobial activity of the fermented juice was determined using microtiter plate assays, and the bioactive metabolites were identified using 1H NMR metabolomics analysis. Fermented juice was added to fresh juice at different ratios including 10:90, 20:80 and 30:70 (v/v) to determine the effects on the shelf life and sensory properties. Fermented cantaloupe juice demonstrated strong antibacterial activity against Escherichia coli, Salmonella typhimurium, Aspergillus flavus and Penicillium spp. The 1H NMR metabolomics profiling identified 23 metabolites in fermented and non-fermented cantaloupe juice. The PCA model demonstrated significant discrimination level between the fermented and non-fermented cantaloupe juice. The metabolites responsible for the discrimination were lactic acid, GABA, acetoin, acetoacetate, cellobiose and alanine in the fermented cantaloupe juice, and sucrose, glucose, mannose and epicatechin in non-fermented cantaloupe juice. The ratio 20:80 of fermented cantaloupe juice to the fresh juice extended the shelf life for 6 months at 8 °C and sustained good sensory properties for cantaloupe juice. The findings of this study showed high potential for the fermented cantaloupe juice to be added to the fresh cantaloupe juice as natural preservative to extend the shelf life and improve the sensory properties.